Corrosion and tribocorrosion behavior of Ti-Alumina composites - Gordo, Elena (2016)
This work focus on the corrosion and wear properties of titanium reinforced with 1% wt. alumina particles, produced by a combination of colloidal techniques and powder metallurgy. The alumina particles were added to control the grain growth of titanium during sintering, and simultaneously to increase hardness and wear resistance. Colloidal techniques permitted a homogeneous dispersion of alumina particles on the surface of fine Ti particles by the formulation of stable aqueous suspensions that were further processed by spray-dry to obtain spherical granules with improved compressibility. Ti-Alumina samples were produced by uniaxial pressing of granules and vacuum sintering leading to materials with homogeneous microstructure, a reduction of grain size higher than 50 % with respect to pure titanium, and a sensible increase in hardness. But the addition of ceramic particles can also have an influence on the corrosion behavior that is one of the most interesting properties of titanium alloys, and on wear resistance, that is one of the drawbacks of Ti. Moreover, the study of simultaneous action of wear and corrosion (tribocorrosion) is an area of highest interest in applications like biomedical or automotive. The corrosion behavior was evaluated by Electrochemical Impedance Spectroscopy (EIS) and Potentiodynamic Polarization (PP) in NaCl at two concentrations (0.9 % and 3.5 %) and temperatures (37 °C, and room temperature). Tribocorrosion tests were performed using a reciprocating ball-on-plate tribometer where a 10 mm diameter alumina ball was used as counter material, and 10 N normal load was applied during 30 min in the same concentrations and temperatures of NaCl as in the static corrosion test s. The results showed a clear improvement of wear resistance on the composite without reducing the corrosion behavior in both conditions.